2013
DOI: 10.1093/jac/dkt285
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of time-to-positivity in aerobic and anaerobic vials to predict the presence of Candida glabrata in patients with candidaemia

Abstract: Using the BACTEC 9240 system, a TTP ≤ 56.5 h is useful to rule out C. glabrata. In addition, in settings with an ~12% prevalence of C. glabrata candidaemia, yeast detection exclusively or earlier in anaerobic vials increases the probability of the presence of C. glabrata to 58%, which may be useful for early treatment optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Potential explanations are an unequal distribution of catheter-related candidemia between sites and different proportions of patients undergoing antifungal therapy at the time when blood samples for culture were drawn. In any case, our data indicate caution about the use of absolute cutoff values for TTP in predicting C. glabrata as has been proposed in other studies (8)(9)(10).…”
supporting
confidence: 44%
See 1 more Smart Citation
“…Potential explanations are an unequal distribution of catheter-related candidemia between sites and different proportions of patients undergoing antifungal therapy at the time when blood samples for culture were drawn. In any case, our data indicate caution about the use of absolute cutoff values for TTP in predicting C. glabrata as has been proposed in other studies (8)(9)(10).…”
supporting
confidence: 44%
“…In patients with candidemia, the TTP has been reported to be longer for Candida glabrata than for other Candida species in BacT/Alert (6,7) and Bactec 9240 systems (8)(9)(10). Previous works showed that C. glabrata is particularly prone to grow in anaerobic blood culture vials (11,12), and two clinical studies reported that an exclusive or earlier growth in anaerobic vials is useful for predicting C. glabrata (8,13). However, while both clinical studies showed a high specificity, the sensitivity was 37% in one and 95% in the other.…”
mentioning
confidence: 99%
“…The characteristics of episodes with a TTP 24 h in our cohort varied in their microbiology and source of infection in comparison with those with TTP <24 h. As expected, Candida sp. and anaerobic GNB had slow TTP [31,32], and were the main pathogens among this group. This finding underlines the need to optimize microbiological techniques for faster yeast detection [33].…”
Section: Discussionmentioning
confidence: 85%
“…The exceptional results reported by Park et al [ 10 ] showed that the Aerobic medium spiked with C. glabrata remained negative, whereas the Anaerobic medium was 100 % positive. Recently, Cobos-Trigueros et al [ 16 ] analyzed the detection of C. glabrata on BACTEC Aerobic and Anaerobic media (without Mycosis) in a large number of candidemia cases. The authors found that the presence of C. glabrata can be predicted on the basis of exclusive or earlier detection of fungal growth in Anaerobic vials, but the method was characterized by low sensitivity, in the range 31–38 %.…”
Section: Discussionmentioning
confidence: 99%